Investigating contrast sensitivity as part of the assessment of visual requirements for driving - Myburgh, Liani (University of the Free State, 2023)
𝗕𝗮𝗰𝗸𝗴𝗿𝗼𝘂𝗻𝗱: The visual environment around a driver is altered by many factors such as weather, sun or light. Motor vehicle drivers need to be adaptable to different conditions and environments. Ninety percent of a driver’s sensory stimuli is interpreted by the visual system and a healthy functioning visual system is of utmost importance for a driver. Visual requirements for driving, currently, have no known global regulatory body and different visual requirements for drivers are found across the globe. In South Africa, two of the International Council of Ophthalmology (ICO) recommended visual requirements, are included (ICO, 2006). Current requirements include visual acuity (VA) and visual fields (VFs), but contrast sensitivity (CS) has been neglected from the requirements of vision for driving. The addition of CS is a valuable contributor to visual function, especially where different environmental conditions are concerned. Contrast sensitivity provides supplementary information about high contrast VA measurements, which may provide a better representation a driver’s vision in low light conditions such as dusk or dawn. 𝗣𝘂𝗿𝗽𝗼𝘀𝗲: The main aim of the study was to determine if motor vehicle drivers, who obtained their driver’s licences legally by passing the visual requirements for driving in South Africa (SA), would also be able to pass the criteria of a minimum CS requirement of 1.25 Log for each eye, as per Owsley et al. (2001) and Spreng et al. (2018). The importance of a driver requiring an optimal functioning visual system, representative under all types of light and contrast conditions, becomes evident in the constantly changing environmental conditions a driver faces during the act of driving. While VA is representative of vision during high contrast conditions, CS may better represent vision in low contrast conditions. 𝗠𝗲𝘁𝗵𝗼𝗱𝗼𝗹𝗼𝗴𝘆: This descriptive research study design recruited 110 participants, using a convenience sampling method. All participants were in possession of a valid South African driver’s license. To investigate whether additional visual requirements, such as CS should be included in the requirements for driving in SA, the current visual requirements (VA and VFs) as well as CS as an additional requirement, were investigated for possible associations with five variables (licence type, age, gender, known/diagnosed pathology, and previous ocular surgery). 𝗥𝗲𝘀𝘂𝗹𝘁𝘀: Thirteen point six percent of valid licenced drivers of the study population did not fulfil the visual requirements for their specific licence type at the time of data collection. Contrast sensitivity indicated statistically significant associations (p-value = ≤ 0.05) with age (p-value = 0.00 both eyes), licence type (p-value = right eyes 0.01, left eyes 0.00), known/diagnosed pathology (p-value = 0.00 both eyes), and previous ocular surgeries (p-value = 0.00 both eyes). Thus, CS measurements may be influenced by different licence types, age, known/previously diagnosed pathology, and previous ocular surgery. Arguably, if all participants were corrected to obtain a pass criterion for their specific visual requirements for driving (VA and VFs), 7.3% of these participants would still have failed the requirements if an additional minimum requirement of 1.25 Log for CS was included. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻: Contrast sensitivity is an important and underrated visual function, especially in changing light conditions, not currently evaluated in the requirements for driving in South Africa. Contrast sensitivity is of clinical significance and may affect safe driving behaviour. The quality of vision of a driver may be compromised in the presence of reduced CS, even in the presence of good clinical VA and acceptable VFs.
Dissertation(MOptom.(Optometry))--University of the Free State, 2023
Keywords: Visual acuity; Temporal visual fields; Total horizontal visual fields; Contrast sensitivity; Visual requirements; South African driver’s license; International Council of Ophthalmology (ICO); South Africa; Pelli-Robson; Visual requirements for driving